Early Proliferation Does Not Prevent the Loss of Oligodendrocyte Progenitor Cells during the Chronic Phase of Secondary Degeneration in a CNS White Matter Tract - Payne, S.; Bartlett, C.; Savigni, D.; Harvey, A.; Dunlop, S.; Fitzgerald, Melinda (Public Library of Science, 2013)
Partial injury to the central nervous system (CNS) is exacerbated by additional loss of neurons and glia via toxic events known as secondary degeneration. Using partial transection of the rat optic nerve (ON) as a model, we have previously shown that myelin decompaction persists during secondary degeneration. Failure to repair myelin abnormalities during secondary degeneration may be attributed to insufficient OPC proliferation and/or differentiation to compensate for loss of oligodendrocyte lineage cells (oligodendroglia). Following partial ON transection, we found that sub-populations of oligodendroglia and other olig2+ glia were differentially influenced by injury. A high proportion of NG2+/olig2–, NG2+/olig2+ and CC1−/olig2+ cells proliferated (Ki67+) at 3 days, prior to the onset of death (TUNEL+) at 7 days, suggesting injury-related cues triggered proliferation rather than early loss of oligodendroglia. Despite this, a high proportion (20%) of the NG2+/olig2+ OPCs were TUNEL+ at 3 months, and numbers remained chronically lower, indicating that proliferation of these cells was insufficient to maintain population numbers. There was significant death of NG2+/olig2– and NG2−/olig2+ cells at 7 days, however population densities remained stable, suggesting proliferation was sufficient to sustain cell numbers. Relatively few TUNEL+/CC1+ cells were detected at 7 days, and no change in density indicated that mature CC1+ oligodendrocytes were resistant to secondary degeneration in vivo. Mature CC1+/olig2– oligodendrocyte density increased at 3 days, reflecting early oligogenesis, while the appearance of shortened myelin internodes at 3 months suggested remyelination. Taken together, chronic OPC decreases may contribute to the persistent myelin abnormalities and functional loss seen in ON during secondary degeneration.